Analysis Of Public Relations Strategy In Maintaining Customer Trust: Study at PT. Bumiputera Sharia Life Insurance Kediri Branch - Cahya Intanesia, Indah; Andriani; Hariyanti, Sri (Benefits : Jurnal Ekonomi dan Pariwisata Internasional, 2025)
A state-owned insurance company owned by a State-Owned Enterprise (BUMN) with indications of losses of 13.7 trillion which had a systemic impact on the Indonesian economy. The negative stigma regarding insurance is so difficult to eliminate that it has an impact on public trust in the sharia insuranceindustry. PT. Bumiputera Sharia Life Insurance Kediri was affected by the national crisis-trust, the result in claims debt costs arised. The purpose of this research is to analyze the public relations strategy of PT. Bumiputera Sharia Life Insurance Kediri in maintaining customer trust. This research is qualitative type using descriptive analysis. The data taken is primary data and secondary data. This research uses case studies that obtain observation data on an object and from various sources such as books, scientific articles, official websites, and data reports on the objects studied. The results of this research explain that strategy public relations used by PT. Bumiputera Sharia Life Insurance, Kediri branch, namely making an apology, stopping marketing until the problem is resolved, encouraging a positive track record, and appointing an unofficial spoke person. The role of strategy public relations PT. Bumiputera Sharia Life Insurance, Kediri branch, still has customers who persist and regularly pay premiums, amounting to 96% of the total number of customers or 2,014 surviving customers.